2022
DOI: 10.1002/nop2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term care facilities' response to the COVID‐19 pandemic: A protocol of a cross‐sectional, multi‐site, international survey

Abstract: Aim To examine the response of long‐term care (LTC) residential facilities to the COVID‐19 pandemic worldwide, and the antecedents and outcomes of this response. Design A protocol of a cross‐sectional survey. Methods Two online questionnaires will be used to collect data from LTC residential facilities' managers and staff worldwide. Collected data include participants' socio‐demographic characteristics, facility‐related characteristics, facility response to the COVID‐19 pandemic, and possible influences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The methods and conducts of the current study were described in a published protocol (Eltaybani et al, 2022) and are summarized below. The study was reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (von Elm et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods and conducts of the current study were described in a published protocol (Eltaybani et al, 2022) and are summarized below. The study was reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (von Elm et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Due to time and resource limitations, the validation process took place through online discussions with experts and no pilot studies were conducted. The questions and their response options and scoring were described elsewhere (Eltaybani et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations